Characterization of Glycoproteins of Native 19kDa C-Terminal Merozoite Sur-face Protein-1 from Native Antigen of Plasmodium falciparum - Sahar Tajik; Sedigheh Sadeghi; Ayda Iravani; Mitra Khalili; Mohammad Arjmand; Nassir-Ud Din; Farideh Vahabi; Hossein Feiz-Haddad; Behzad Lame-Rad; Saeid Reza Naddaf; Zahra Zamani (Tehran University of Medical Sciences, 2019)
Background: Plasmodium falciparum is the protozoan parasite which causes malignant malaria of medical concern. Prime candidates for recombinant vaccine development are asexual stage antigens of P. falciparum, for example, merozoite surface proteins (MSP1 and MSP2) not given satisfactory results to date. In this study, the 19kDa C-terminal of MSP1, a vaccine candidate was purified in its native form in the ring stage, and its glycoproteins studied. Methods: The study was carried out at the Biochemistry Department of Pasteur Institute of Iran in the years 2015-2016. Large scale culture of P. falciparum was performed in vitro with 80% ring stage parasitemia. Isopycnic ultracentrifugation with 36% sucrose and analytical SDS-PAGE on the supernatant and precipitate performed, and the 19kDa antigen was obtained by cutting it from strips of preparative SDS gels. Purified protein was concentrated and analyzed by SDS-PAGE and immunoblotting, using antibodies raised to recombinant C-terminal MSP1. Results: The purified protein gave a single band of 19kDa antigen as shown by silver staining of SDS-PAGE and a single bond in immunoblotting. Bioinformatics also confirmed the likelihood of the presence of glycans on the antigen. Conclusion: The presence of N and O-glycoproteins were detected by Q proteome kit. This work was done on the ring stage, and earlier workers confirmed the presence of glycoproteins on MSP1 in the other stages. This glycosylation is present in all stages, and maybe incomplete protection elicited by recombinant MSP1 antigens is due to lack of N and O-glycoproteins.